Analisis Kapabilitas Sistem Pelayanan Pelanggan Menggunakan Framework Cobit 5 (Studi Kasus: Pdam Sidoarjo) - Safitri, Eristya Maya; Safira, Amalia; Wardinasahira, Putrinadiffa; Ertiansyah, Ahmad Alfian; Cintani, Nadia Latifa; Naja, Safinatun; Ahmad, Naufal Nur (Jurnal Kridatama Sains dan Teknologi, 2024)
Customer service is a crucial element in the operations of Regional Water Supply Companies (PDAM) to ensure customer satisfaction and support business sustainability. This study aims to evaluate the capabilities of the customer service system at PDAM Sidoarjo, which still relies on manual processes, particularly in managing customer complaints and meter readings. Although bill payments have been integrated with the Payment Point Online Bank (PPOB) system, the manual processes still pose challenges, such as data errors and processing delays. An audit was conducted using the COBIT 5 framework, focusing on domains DSS01 - Manage Operations, DSS02 - Manage Service Requests and Incidents, and MEA01 - Monitor, Evaluate, and Assess, to assess the capability levels and identify areas for improvement. The audit results indicate that the average capability level of DSS01 is at Level 4 (Predictable Process), while DSS02 and MEA01 are at Level 3 (Established Process) and Level 4, respectively. The gap analysis revealed the need for improvements in infrastructure monitoring, complaint handling, and service quality evaluation. Recommendations include process automation and enhanced oversight to achieve better efficiency and effectiveness. This research is expected to serve as a guide for PDAM Sidoarjo in improving the capabilities of its customer service processes to support more optimal and customer-oriented services.